Spontaneous unscarred fundal rupture after normal vaginal delivery - Thapa, Shreya; Rani, Anjali; Pandey, Uma; Agrawal, Nisha Rani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Uterine rupture is one of the most dangerous obstetric situation carrying an increased risk of maternal and perinatal morbidity and mortality, associated with poorly managed labour. The incidence of spontaneous rupture of unscarred uterus is around 1 in 8000 to 1 in 15000 deliveries. We report this unusual case of spontaneous unscarred fundal rupture after normal vaginal delivery. This case under reference developed shock soon after delivery and was explored due to suspected intraperitoneal hemorrhage. This case is being reported to emphasis the need for proper post-delivery monitoring not only to diagnose post-partum hemorrhage but also to suspect uterine rupture as a cause of unexplained shock developing after delivery inspite of all resuscitative measures. Although unexpected in a woman with an unscarred uterus, rupture should be considered as a possible cause of unusual pain or hypotension in the mother. The most effective way to reduce the number of morbidity and mortality would be to prevent unwanted pregnancies by informed and effective use of contraception.